78 Effects of short-term omission or increase in loop diuretic therapy on cardiac function in patients with chronic, stable heart failure. (May 2019) - Khan, Muhammad; Pellicori, Pierpaolo; Cleland, John GF
Abstract : Background: The effects of short-term variations in loop diuretic (LD) agents on haemodynamics in patients with chronic, stable heart failure has rarely been studied. Purpose: To investigate the effects of increasing or omitting LD for 48 hours on clinical, biochemical and echocardiographic variables in patients with chronic, stable heart failure and a reduced left ventricular ejection fraction (LVEF <50%). Methods: Patients were studied on two occasions and observed for 3 hours following oral administration of their usual daily dose of LD. Echocardiography, weight and blood pressure assessments were performed hourly. Results: Eight patients [mean age 67 (7) years, 75% NYHA I/II, 50% men, 25% in atrial fibrillation] were enrolled. Compared to omitting LD, increasing LD reduced plasma NT-proBNP (from 644ng/L to 369 ng/L; p=0.017), left ventricular end-diastolic volume (LVEDV, from 188 ml to 162 ml, p=0.045), left atrial volume (LAV, from 82 ml to 73 ml, p=0.007) and systolic (from 133mmHg to 116mmHg, p=0.005) and diastolic (from 74mmHg to 64mmHg, p=0.043) blood pressure, and increased haemoglobin (from 129 g/L to 136 g/L, p=0.028), haematocrit (0.40% to 0.42%, p=0.04), serum urea (6.3 mmol/L to 9.6 mmol/L, p=0.008) and the ratio of jugular vein diameter after Valsalva to that at rest by ultrasound (JVD ratio, from 5.6 to 6.6, p=0.043). There was no significant change in body weight, serum creatinine or LVEF. Significant reductions on LVEDV and LAV and an increase in JVD ratio were evident within one hour from oral LD administration and persisted after 3 hours, without a change in body weight or blood pressure. These acute effects of LD administration on echocardiographic variables were more pronounced when patients had previously had their diuretic therapy omitted for 48h. Conclusion: LD have important and rapid effects on intra-cardiac and vascular volume. This has important implications for the conduct of clinical trials that use changes in cardiac volumes or NT-proBNP as measures of cardiac remodelling and/or therapeutic benefit. Conflict of Interest: None